The Impact of EDTA And Selenite on The Stability of Insulin in Cell Culture Media - A. S. Prakasha Gowda; Andrew D. Schaefer; Terry K. Schuck (International Journal of Biochemistry Advances, 2023)
Insulin is a frequent peptide hormone addition in serum-free mammalian cell culture media. It contributes in a variety of biological functions, including as promoting cell proliferation, cell cycle progression, and glucose uptake. However, it is unknown how stable insulin is under in vitro cell culture media treatment conditions. The instability of insulin in aqueous solutions has caused a number of issues, necessitating the development of new therapeutic strategies that can keep insulin stable and functioning. Such choices are required to accommodate updated insulin delivery guidelines as well as the storage and transportation of insulin. To preserve structural and functional integrity, protein medicines are frequently stabilized with antioxidants in aqueous solutions. In the present study, the effects of the antioxidants disodium ethylenediaminetetraacetic acid dihydrate (EDTA) and sodium selenite (Se) and their ability to scavenge free radicals on insulin stability in the medium Dulbecco's Modified Eagle Medium (DMEM) and Roswell Park Memorial Institute (RPMI) were examined. To investigate the stability of human recombinant insulin, in vitro serum-free DMEM and RPMI media were utilized for 5 days at 37˚C containing different EDTA and Se concentrations. Reversed phase high performance liquid chromatography (RP-HPLC) was used to detect and quantify insulin. Sodium dodecyl sulfate polyacrylamide gel (SDS-PAGE) electrophoresis was used to assess conformational stability. The results demonstrated that, when EDTA and Se were added separately to DMEM and RPMI media, insulin stability was improved compared to when neither compound was added.
Keywords: Insulin Stability